2018
DOI: 10.1016/j.jpsychires.2018.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Principal component analysis of early alcohol, drug and tobacco use with major depressive disorder in US adults

Abstract: Early alcohol, tobacco and drug use prior to 18 years old are comorbid and correlated. This study included 6239 adults with major depressive disorder (MDD) in the past year and 72,010 controls from the combined data of 2013 and 2014 National Survey on Drug Use and Health (NSDUH). To deal with multicollinearity existing among 17 variables related to early alcohol, tobacco and drug use prior to 18 years old, we used principal component analysis (PCA) to infer PC scores and then use weighted multiple logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
0
7
0
5
Order By: Relevance
“…To verify the third assumption, we employed additional MR analysis to investigate whether genetic predisposition towards HGS is associated with the potential confounders underlying the affecting factors of HGS. For instance, more alcohol consumption is related to both reduced HGS13 and increased risk of MDD 14. Larger waist circumference was frequently found in patients with MDD, compared with the general population 15.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify the third assumption, we employed additional MR analysis to investigate whether genetic predisposition towards HGS is associated with the potential confounders underlying the affecting factors of HGS. For instance, more alcohol consumption is related to both reduced HGS13 and increased risk of MDD 14. Larger waist circumference was frequently found in patients with MDD, compared with the general population 15.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, more alcohol consumption is related to both reduced HGS 13 and increased risk of MDD. 14 Larger waist circumference was frequently found in patients with MDD, compared with the general population. 15 In addition, an independent negative association was found between HGS and metabolism-related markers, including waist circumference, triglycerides, high-density lipoprotein cholesterol (HDL-C), glucose and blood pressure (BP).…”
Section: Statistical Analysis For Mrmentioning
confidence: 96%
“…Adolescent illicit substance use has been reported to elevate the risk of anxiety and mood disorder (Fergusson et al, 2002; Sareen et al, 2006; Wang et al, 2018). Moreover, adolescent smoking and frequent intoxication has been associated with SUD in young adulthood (Riala et al, 2004; Sarala et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review 19 reports an association between smoking and major depression and the tendency of people with depression and anxiety to be heavy smokers. A study carried out in the United States found that the use of tobacco, alcohol and other drugs before the age of 18 is associated with an increased risk of depression in adulthood 20 . Additionally, MDs are associated with heavy smoking, greater degree of nicotine dependence, increased withdrawal symptoms, and lower cessation rates.…”
Section: Smokingmentioning
confidence: 99%